Beyond cybersecurity : protecting your digital business - Kaplan, James M.; Bailey, Tucker; Rezek, Chris; O'Halloran, Derek; Marcus, Alan (Hoboken, New Jersey : Wiley, 2015)
Annotation Protecting your digital assets is no longer a technical conversation alone, but one that should involve the Board and senior executives. This study offers concrete, actionable and business-wise recommendations to strengthen cyber resilience.
Cyber-attacks Jeopardize Companies' Pace of Innovation -- It Could Get Better; or $3 Trillion Worse -- Prioritize Risks and Target Protections -- Do Business in a Digitally Resilient Way -- Modernize IT to Secure IT -- Engage Attackers with Active Defense -- After the Breach: Improve Incident Response across Business Functions -- Build a Program that Drives toward Digital Resilience -- Creating a Resilient Digital Ecosystem.
Includes index.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed April 21, 2015).
Keywords: Computer security; Computer networks -- Security measures; Computer networks -- Access control; Internet -- Security measures; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Computer networks -- Access control; Computer networks -- Security measures; Computer security; Internet -- Security measures; Business; Nonfiction; Electronic books; Electronic books